2010
DOI: 10.1038/ejcn.2010.151
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to recommendations of the German food pyramid and risk of chronic diseases: results from the EPIC-Potsdam study

Abstract: Background: The German food pyramid was set up to foster and communicate healthy food choices. Methods: The adherence to recommendations of the food pyramid was translated into an index (German Food Pyramid Index (GFPI)) by scoring the ratio of consumed and recommended daily servings of eight food groups, wherein higher scores indicated greater adherence. The GFPI was calculated for 23 531 subjects who participated in the European Prospective Investigation into Cancer and Nutrition-Potsdam study and were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 26 publications
2
42
0
1
Order By: Relevance
“…When evaluating adherence to specific NFG recommendations, we further distinguished between food groups whose recommendations refers to (1) a minimum, (2) a range, or (3) a maximum of intake (see Figure 1), as described below, which is in line with the scoring algorithm of the German HEI [27]. …”
Section: Methodsmentioning
confidence: 99%
“…When evaluating adherence to specific NFG recommendations, we further distinguished between food groups whose recommendations refers to (1) a minimum, (2) a range, or (3) a maximum of intake (see Figure 1), as described below, which is in line with the scoring algorithm of the German HEI [27]. …”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, most diet indexes have not predicted total cancer incidence(15) or total cancer mortality,(6, 7) with some exceptions. (810) However, in most cases lifestyle indexes that add other modifiable risk factors such as body weight, physical activity and smoking have been found to predict total cancer incidence(11–14) and mortality.…”
Section: Introductionmentioning
confidence: 95%
“…The few available data suggest that adherence to the aHEI [11], the Dietary Approaches to Stop Hypertension (DASH) diet [12, 13], the HEI [11] and the Overall Nutritional Quality Index (ONQI) [14] may lower diabetes risk. No clear associations were observed for the Recommended Food Score [12], the Diet-Quality Index [15] and diet-quality scores, reflecting guidelines from Germany [16] and Australia [17]. Most of these studies were conducted in American populations [1115] and it has been suggested that associations may differ between heterogeneous populations such as different ethnic groups [13, 15].…”
Section: Introductionmentioning
confidence: 99%